ESTIMATION OF THE BEST LINEAR UNBIASED PREDUCTION (BLUP) OF RAMS DEPENDING ON THEIR PROGENY’S BIRTH AND WEANING WEIGHT - & et al., Raoof (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in a private sheep herd at Kurdistan region- Iraq during the period from June/2015 to Augest/2016. A total of 189 ewes and 9 rams were used and aimed to study the effect of some non-genetic factors (age of dam,sex and type of birth, estrous sequences cycle and ewes weights at lambing ) on the birth and weaning weights. The heritability and the best liear unbiased preduction (BLUP) were estimated. The overall means of the birth and weaning weights were 3.90 and 24.25 kg respectively.The results showed that the birth weight and weaning weight were significantly ( p<0.05) affected by age of dam, sex and type of birth, estrous sequences cycle and ewes weights at lambing. The ewes of age≥5 yeares were exceed on other ewes ages concerning the birth and weaning weights of lambs. It was shown that the effect of the estrous sequences cycle of ewes was significant (P<0.05) on the weaning weights of lambs, as the mean lambs birth weight was 4.08 and 3.18 kg for the ewes in the first and second estrous cycle respectively.Also results revealed that the weight of ewe at birth was significant (P<0.05) on the lamb birth weight as the ewes of weight of 46-50 kg were exceed on the ewes of the age ≤45 kg. Heritability estimates of birth, weaning weights and body weight gain were 0.24,0.31 and 0.24 ,respectively. BLUP values of sires for birth weight were between 0.09899 and 0.07730- and weaning weight between 0.2769 and 0.1272- respectively.